Amplification of Positivity Therapy for Co-occurring Alcohol Use Disorder with Depression and Anxiety Symptoms: Pilot Feasibility Study and Case Series. Issue 5 (September 2022) - Akeman, Elisabeth; White, Evan; Wolitzky-Taylor, Kate; Santiago, Jessica; McDermott, Timothy J.; DeVille, Danielle C.; Stewart, Jennifer L.; Paulus, Martin; Taylor, Charles T.; Aupperle, Robin L.
Positive valence system dysregulation is a relatively unexplored transdiagnostic mechanism and potential treatment target underpinning alcohol use and anxiety and depression symptoms. The current study examined the feasibility and potential benefit of a behavioral intervention focused on amplification of positivity (AMP) with eight adults (five female) diagnosed with alcohol use disorder and clinically significant depression or anxiety (ClinicalTrials.gov: NCT04278365). AMP for alcohol use (AMP-A) was delivered in 11 individual sessions involving positive activity interventions integrated alongside psychoeducation and alcohol use monitoring. Case descriptions are provided to illustrate treatment implementation. Treatment credibility and acceptability, participant endorsement of the therapy, and homework compliance were rated moderate to high. Exploratory, intent-to-treat analyses suggested medium to large effect sizes for post-treatment improvements in alcohol use, depression, anxiety, and positive affect. Results provide initial evidence of feasibility and acceptability of AMP-A and will be useful for informing future randomized clinical trials to examine clinical efficacy.